The Electrochemical Behavior of SnSb as an Anode for Li-ion Batteries Studied by Electrochemical Impedance Spectroscopy and Electron Microscopy - Tesfaye, Alexander T.; Yucel, Yasemin D.; Barr, Maissa K. S.; Santinacci, Lionel; Vacandio, Florence; Dumur, Frederic; Maria, Sebastien; Monconduit, Laure; Djenizian, Thierry (Electrochimica Acta, 2017)
Evolution of the electrical and morphological properties of micron-sized SnSb has been investigated to understand the electrochemical behavior observed during cycling experiments. Electron microscopy techniques (scanning electron microscopy and transmission electron microscopy) and electrochemical impedance spectroscopy have been combined to evidence the electrode modifications and particularly the formation of a solid electrolyte interphase (SEI) layer. Evolution of the SEI resistance and the charge transfer resistance with the cell voltage can be explained by the electrolyte degradation and expansion/contraction of the electrode. Furthermore, we show that the SEI formation is not limited at the first discharge/charge of the battery. The continuous growth of the SEI layer up to 50 cycles associated to the electrode pulverization caused by the large volume variations are responsible for the capacity fading.
Created from Fastlane, Scopus look-up
Keywords: Electrochemical Impedance Spectroscopy; Electron Microscopy; Li-ion Batteries; SnSb; Solid Electrolyte Interphase